Influence of up-flow velocity on the performance of an anaerobic filter under oleic acid overloads - Ribeiro, N. J. (2001)
An upflow velocity of 0.21 m h−1 was optimal to minimize the effect of organic shocks (from 6 to 30 kg COD m−3 d−1) when operating an upflow anaerobic filter for the treatment of an oleic acid-based effluent (50% w/v COD). This value represented the transition between a mass transfer controlled regime and a kinetic regime. Under hydraulic shock loads, an increase in upflow velocity from 0.3 to 0.4 m h−1 decreased the removal efficiency from 68 to 51%.